(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
This essay aimed to discuss the influence of phylogenetic aspects in the emergence of religious behavior through a dialogue between Behavior Analysis and Evolutionary Psychology. It’s concluded that the phylogenesis is closely linked to learning processes related to religious behavior, because the human species has developed a biological apparatus that allows animists attributions to the environment, which are often reinforced by increasing the probability of species survival. Lastly, it’s hypothesized that religious behavior emerged in association with other behavioral functions (such as warning systems) linked to species survival, which was not necessarely linked to religiosity, but a biological capacity (of the species) to be reinforced.